Analisis Zakat Profesi dalam Zakat Mal Berdasarkan Kajian Hadis - Rihadatul Aisyi, Gheani; Amelia Putri, Dyah; Dadah, Dadah (El Nubuwwah Jurnal Studi Hadis, 2024)
The phenomenon in society shows that individuals with high incomes, such as lecturers, doctors, and lawyers, often lack awareness regarding the obligation to pay professional zakat. One of the main reasons is the absence of explicit regulations on professional zakat during the time of Prophet Muhammad (PBUH), leading some to believe that it is not mandatory. However, as Islamic jurisprudence evolves, professional zakat has been increasingly examined by scholars and Islamic institutions as a relevant form of zakat in the context of the modern economy. This study aims to analyze the interpretation of hadiths and scholarly opinions regarding the obligation of professional zakat in Islam. The research employs a qualitative method with a library research approach, reviewing various literature sources, classical Islamic jurisprudence books, and fatwas from different schools of thought. According to Yusuf Qaradawi, the threshold (niṣāb) for professional zakat is analogous to gold and silver zakat, set at the equivalent of 85 grams of gold, with a zakat rate of 2.5% on net income. The findings indicate that professional zakat plays a crucial role in enhancing societal welfare, reducing economic disparities, and strengthening social solidarity. Although scholars hold differing views on its obligatory status, professional zakat has been widely endorsed in Indonesia through various fatwas issued by the Indonesian Ulema Council (MUI) and other Islamic institutions. Therefore, professional zakat is not only a religious obligation for Muslims but also serves as an economic instrument to promote equitable and sustainable welfare distribution.